Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Masalah (Problem Based Learning) Pada Materi Haloalkana Untuk Kelas XII SMA/MA - , Suryelita, Mitra susanti (journal of residu, 2019)
The aims of the research is to develop teaching materials in the form of student work sheets (SWS) on haloalkana  problem based learning and to reveal its validity and practicalities. The type of this research is Research and Development with 4-D development models which consists of  define, design, develop, and disseminate. This research is limited to develop stage. The research instrument used a questionnaire validity and practicality. The questionnaire of validity is filled by lecture and teacher. The questionnaire of practicality is filled by students in SMAN 1 Ranah Pesisir. Data from this research will be analyzed using Cohen’s kappa formula. Based on the analysis of questionnaire known that LKPD produced has a very high validity category (κ=0,83); very high practicality (κ=0,88) based on teacher judgement; and high practicality (κ=0,79) based on student judgement. Keywords: haloalkane, Student Worksheets, Problem Based Learning, Research and Development, 4-D Models.